Transmisi harga ikan tuna di Kecamatan Pasarwajo Sulawesi Tenggara - Lipogena, Kifin T.; Riani, Irdam; Alimina, Naslina; Patiung, Seventry Meliana; Lawelle, Sjamsu Alam (Universitas Halu Oleo, 2024)
This research aims to determine the transmission of tuna prices in Pasarwajo District, Southeast Sulawesi. This research was carried out from December 2022 to January 2023, located in Pasarwajo District. The sample of fishermen was taken by census while the sample of retailers used Snowball Sampling. Method data collection by surveys, interviews, and documentation. The data analysis used was quantitative analysis which is explained descriptively using regression formulas and price transmission elasticity analysis. The results showed that in the price change rate of tuna fish at the retailer level was more greater prices change rate at the fisherman level.